Design and Implementation of Home Appliance Energy Monitoring Device - Sanni, Shereefdeen O.; Olusuyi, Kehinde O.; Mahmud, Ismail (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
This paper presents the implementation of an energy monitoring device using Arduino Nano microcontroller to measure the power consumed by any individual electrical appliance in residential homes. It is also designed with the capability of sending measured electrical power parameters through SMS to owners when a request is made. The electrical energy and power are calculated based on measurements taken by Allegro ACS712 Hall effect current sensor and measured voltage over a time period. A novel feature of this device is its ability to also determine the start-up current of inductive loads. The device come in handy for homeowners who want to monitor the energy consumption of some appliances to reduce associated electricity bills. In addition, it could also be used for an energy audit of residential homes.